The Stringent Response Controls Catalases in Pseudomonas aeruginosa and Is Required for Hydrogen Peroxide and Antibiotic Tolerance - Khakimova, Malika (American Society for Microbiology, 2013)
Pseudomonas aeruginosa, a human opportunistic pathogen, possesses a number of antioxidant defense enzymes under the control of multiple regulatory systems. We recently reported that inactivation of the P. aeruginosa stringent response (SR), a starvation stress response controlled by the alarmone (p)ppGpp, caused impaired antioxidant defenses and antibiotic tolerance. Since catalases are key antioxidant enzymes in P. aeruginosa, we compared the levels of H(2)O(2) susceptibility and catalase activity in P. aeruginosa wild-type and ΔrelA ΔspoT (ΔSR) mutant cells. We found that the SR was required for optimal catalase activity and mediated H(2)O(2) tolerance during both planktonic and biofilm growth. Upon amino acid starvation, induction of the SR upregulated catalase activity. Full expression of katA and katB also required the SR, and this regulation occurred through both RpoS-independent and RpoS-dependent mechanisms. Furthermore, overexpression of katA was sufficient to restore H(2)O(2) tolerance and to partially rescue the antibiotic tolerance of ΔSR cells. All together, these results suggest that the SR regulates catalases and that this is an important mechanism in protecting nutrient-starved and biofilm bacteria from H(2)O(2)- and antibiotic-mediated killing.